Zfhx3 decreases expression of cardiac Nav1.5 channels and inhibits sodium current. (14th October 2021) - Caballero, R; Camara-Checa, A; Rubio-Alarcon, M; Crespo-Garcia, T; Dago, M; Nieto-Marin, P; Marin, M; Salguero, R; Toquero, J; Tamargo, J; Cebrian, J; Delpon, E; et al.
Abstract: Background: Zfhx3 (zinc finger homeobox 3) is a transcription factor (TF) encoded by the ZFHX3 gene. GWAS and gene-based association studies showed that ZFHX3 is one of the major atrial fibrillation (AF) susceptibility-conferring genes. The sodium current (INa), carried by Nav1.5 channels encoded by SCN5A, is responsible for atrial and ventricular action potential depolarization and determines cardiac excitability. Zfhx3 interacts with other TFs, such as Tbx5 and Pitx2c that increase and decrease INa, respectively. However, the effects of Zfhx3 on cardiac INa are currently unknown. Purpose: We aimed to determine the effects of Zfhx3 on the INa on HL-1 cardiomyocytes. Methods: cDNAs encoding human Zfhx3 together or not with Pitx2c or Tbx5 were transfected in HL-1 cells. Endogenous Zfhx3 expression in HL-1 cells was silenced by means of siRNAs. INa was recorded at room temperature using the whole-cell patch-clamp and luciferase reporter assays, qPCR and Western-blot (WB) analyses were also conducted. Results: Expression analysis of RNA-seq data from human ventricular (n=432) samples (GTEx) demonstrated that Zfhx3 mRNA can be detected in the adult working myocardium. Transfection of Zfhx3 strongly reduced peak INa density (from −75.0±6.6 to −30.9±2.9 pA/pF; n≥26, P<0.001). In contrast, Zfhx3 silencing augmented INa density compared to cells transfected with scrambled siRNA (from −65.9±8.9 to −104.6±10.8 pA/pF; n≥8, P<0.05). Neither Zfhx3 expression nor silencing modified time and voltage dependence of activation and inactivation or the reactivation kinetics. Zfhx3 significantly reduced transcriptional activity of human SCN5A, PITX2 and TBX5 minimal promoters and, consequently, the mRNA and protein expression levels of Nav1.5, Pitx2c, and Tbx5 were diminished (n≥6, P<0.05). In cells transfected with Zfhx3 together with Pitx2c, but not with Tbx5, INa density was significantly smaller than in cells expressing WT Zfhx3 alone (n≥15, P<0.05). Further WB experiments demonstrated that Zfhx3 increased the expression of Nedd4–2 ubiquitin-protein ligase, which ubiquitinates Nav1.5 channels and favors their proteasomal degradation. Conclusions: Zfhx3 inhibits INa as a result of a direct repressor effect on the SCN5A promoter, the modulation of Tbx5-increasing and Pitx2-decreasing effects on the INa, and the enhancement of Nav1.5 channel degradation. We propose a novel and complex mechanism that regulates the expression of sodium channels and the density of the INa, which are critical for the control of cardiac excitability. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministerio de Economía y CompetitividadComunidad Autόnoma de Madrid